2010
DOI: 10.1111/j.1574-6968.2010.01922.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tRNA composition and folding in psychrophilic, mesophilic and thermophilic genomes: indications for thermal adaptation

Abstract: Comparative genomic studies on several thermophilic archaea and bacteria revealed that a set of coordinated changes are associated with organisms adapted to a higher temperature, among which the dinucleotide composition of genomic DNA, pattern of codon usage and amino acid composition of the proteomes reveal subtle differences between thermophilic and mesophilic organisms. In this context, we have analyzed all tRNA sequences present in the complete genome sequences of 57 organisms belonging to psychrophiles, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…In fact, higher tRNA genes content seem to be related with specific cold adaption mechanisms, as determined by comparative genomics analysis (Dutta and Chaudhuri, 2010). In addition, the number of genes involved in signal transduction mechanisms and inorganic ion transport and metabolism (two COG categories) in this bacterium's genome, is similar to other P. putida strains but exceeds that displayed by other Gammaproteobacteria (Wu et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, higher tRNA genes content seem to be related with specific cold adaption mechanisms, as determined by comparative genomics analysis (Dutta and Chaudhuri, 2010). In addition, the number of genes involved in signal transduction mechanisms and inorganic ion transport and metabolism (two COG categories) in this bacterium's genome, is similar to other P. putida strains but exceeds that displayed by other Gammaproteobacteria (Wu et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…While several studies in both archaea (58) and bacteria (59,60) have shown that the nucleotide content of tRNA genes does not comply with the genomic GC content but is rather restricted by habitat temperature through constraints on folding stability, the wobble position, which does not contribute to structure stability, might be free from these constraints and conform to nucleotide content bias.…”
Section: Discussionmentioning
confidence: 99%
“…In thermophilic organisms, a bias towards GC-rich sequences is frequently observed, and the corresponding tRNAs are GC-rich as well [18,59,60,61,62]. This introduces a folding problem similar to the one observed for AU-rich sequences.…”
Section: Structural Impact Of Modificationsmentioning
confidence: 99%
“…Hence, organisms thriving at high temperatures have an urgent need for thermal stabilization of their tRNAs. One predominant temperature-dependent adaptation is the increase of the GC-content especially in the stems of the cloverleaf structure [60,61]. Oshima reported that an increase of 5% in the GC-content raises the melting temperature of a tRNA by 1.5 °C [62].…”
Section: Modifications and Temperature Adaptationmentioning
confidence: 99%